Una provincia contra su gobernador - Daniel Gutiérrez Ardila (Nuevo mundo - Mundos Nuevos, 2010)
The resources that Creoles in Nueva Granada had to fight against the abuses of royal functionaries after the abdications of Bayonne were essentially inoperable given the constant suspicion that any action they took to protest those events were surreptitious revolutionary projects, that is, crimes of treason. This article analyzes the complexity of this difficult situation as well as the networks which sustained local Creole power on the eve of the revolution in New Granada through an examination of a failed conspiracy.